Exegesis and Screenplay for a Film Entitled: Stolen Innocence - Lee, Melissa (Auckland University of Technology, 2007)
This screenplay is a fictional representation of the holocaust-like atrocities the Japanese inflicted upon 200,000 Korean women during WWII. It is also a reaction to the Japanese government's continued denial of these events and the suffering their denial causes the Korean women who were known as "Comfort Women". The "Comfort Brigade" was the brainchild of Japan's Ministry of Home Affairs, Ministry of Foreign Affairs, other government organisation and military Generals who via a secret document called "Chosun (Korean counter plan" which includes a clause: "Unmarried women in Chosun shall be used to supply the military's special business". The military's "special business" was sexual slavery and the atrocities were so heinous and unrelenting that it couldn't all be written into one screen play. To write it all would also mean an exploitation of the women's suffering. This is a screenplay written from the heart yet derived from historical fact. It is political in its revelation, to the world, what many Japanese continue to deny.
Keywords: Motion picture plays